Characterization of magnetron co-sputtered W-doped C-based films - Silva, C. W. Moura e (2006)
In this paper, W-doped C-based coatings were deposited on steel and silicon substrates by RF magnetron sputtering, using W and C targets, varying the cathode power applied to the W target and the substrate bias. The chemical composition was varied by placing the substrates in a row facing the C and W targets. W content in the films increased from 1 to 2 at.% over the C target to ~ 73 at.% over the W target. The coatings with W content lower than ~ 12 at.% and ~ 23 at.%, for biased and unbiased conditions, respectively, showed X-ray amorphous structures, although carbide nanocrystals must exist as shown by the detection of the WC1-x phase in films with higher W content. C-rich films were very dense and developed a columnar morphology with increasing W content. An improvement in the hardness (from 10 GPa, up to 25 GPa) of the films was achieved either when negative substrate bias was used in the deposition, or when the WC1-x phase was detected by X-ray diffraction. The adhesion of the coatings is very low with spontaneous spallation of those deposited with negative substrate bias higher than 45 V. Varieties in cathode power (90 W or 120 W) applied to the W target showed no observable influence on the characteristics of the films.